Multi Level Marketing (MLM) Syariah: Solusi Praktis Menekan Praktik Bisnis Riba, Money Game - Arum, Imam Mas (IAIN Salatiga, 2012)
The sharia economy and bussines has been acknowledged as an alternativereplacement for socialist and capitalist economy. Sharia banking, insurance and capital market have developed rapidly and accepted widely throughtout the world. Together with the development of knowlegde, technology, and the need of economy, innovation in sharia business continues to emerge. One of them is Sharia MLM or Penjualan Langsung Berjenjang Syariah (PLBS). The booming of riba business money game practic is one of the reason why MLM Sharia was borned. Hopefully it can to be solution for this problem specially in Indonesia. This article discuss about money game, MLM, and prospect of MLM Sharia in force money game practic